2015
DOI: 10.9721/kjfst.2015.47.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Lactic Acid Bacteria (LAB) in Makgeolli and Their Production of γ-Aminobutyric Acid

Abstract: Makgeolli is made from rice or flour, yeast, and nuruk, a fermentation starter. The flavor of makgeolli is affected by sugars, amino acids, organic acids and volatile flavor compounds produced by various microorganisms. In this study, lactic acid bacteria (LAB) were isolated from unsterilized makgeolli samples collected from several provinces in Korea, and then later identified. Under anaerobic conditions, LAB density ranged from 5.0×10 6 to 1.5×10 8 CFU/mL; yeast density ranged from 2.5×10 7 to 1.5×10 8 CFU/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
2
1
0
Order By: Relevance
“…Figure 5 A showed that with increasing the concentration of monosodium glutamate and increasing the temperature, the amount of GABA formed increased. This trend is in agreement with the results reported elsewhere by other authors 41 , 42 .
Figure 5 3D plots showing the interaction effect of three variables for GABA production by Lac.
…”
Section: Resultssupporting
confidence: 94%
“…Figure 5 A showed that with increasing the concentration of monosodium glutamate and increasing the temperature, the amount of GABA formed increased. This trend is in agreement with the results reported elsewhere by other authors 41 , 42 .
Figure 5 3D plots showing the interaction effect of three variables for GABA production by Lac.
…”
Section: Resultssupporting
confidence: 94%
“…In a Makgeolli produced using modified-nuruk, the numbers of LAB and yeast cells during fermentation were approximately 7 and 8 log CFU/mL, respectively (14). Consistent with the results of the present study, the numbers of LAB and yeast cells in raw Makgeolli from the market were 5-7 and 7-8 log CFU/mL, respectively (24,25). Although millimeter waves are known to affect microbial growth, both increased and decreased growth of the same microorganisms depending on the fermentation conditions have been reported (26).…”
Section: Resultssupporting
confidence: 91%
“…In general, fungi are not detected during Makgeolli fermentation, and the major microorganisms are known to be yeasts and LAB (14,24,25). In a Makgeolli produced using modified-nuruk, the numbers of LAB and yeast cells during fermentation were approximately 7 and 8 log CFU/mL, respectively (14).…”
Section: Resultsmentioning
confidence: 99%